Fire extinguishment behaviors of liquid fuel using liquid nitrogen jet. Issue 4 (22nd February 2016) - Shi, Bobo; Zhou, Fubao
Abstract : Liquid nitrogen for liquid fuel fires extinguishing is still a new and hot topic. Fire extinguishment behaviors of liquid nitrogen are not yet fully understood, and the related research is still in its infancy. In this article, a flexible liquid nitrogen jet system was set up to examine the process of liquid nitrogen interacting with the pool fire in an open space. The main objective of this article is to compare the extinguishment behaviors of vertical/horizontal jet of liquid nitrogen for extinguishing oil pool fires by the measurements of weight, thermocouples temperature, and infrared thermal image. As a result, experiment discovered that liquid nitrogen has a satisfactory performance for the pool firefighting. And the horizontal jet of liquid nitrogen is more effective than the vertical jet in terms of fire extinguishing time and the required amount of liquid nitrogen. The shape of fire flame during the period of horizontal liquid nitrogen jet was completely different from that during the period of vertical liquid nitrogen jet. The fire extinguishing mechanism of vertical/horizontal liquid nitrogen jet was revealed, respectively. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 407–413, 2016